Narrative Pedagogy and Student Identity: Exploring Self-Expression in Classroom Storytelling Projects - Carlos Martins; Lusiana Rahmadani Putri; Syilvia Wenny J; Siti Aisyah Hanim (Yayasan Adra Karima Hubbi, 2025)
Background. In recent years, storytelling has gained recognition as a powerful pedagogical approach that supports reflective learning, self-expression, and identity formation. Purpose. This study sought to explore how classroom storytelling projects facilitate students’ reflective engagement and contribute to the construction of personal and academic identities in higher education contexts. Method. Using a qualitative narrative inquiry design, data were collected from 24 university students and 3 lecturers through semi-structured interviews, reflective journals, and storytelling artifacts. The data were analyzed thematically to examine patterns of self-expression, transformation, and relational meaning-making. Results. The findings indicate that storytelling practices enabled students to articulate personal experiences in relation to academic content, enhancing self-awareness, empathy, and communicative confidence. Narrative engagement also fostered emotional literacy and a stronger sense of belonging, transforming the classroom into a dialogic and ethically grounded learning space. Conclusion. The study concludes that narrative pedagogy humanizes the learning process by integrating reflection, identity construction, and ethical understanding. Storytelling emerges as a vital pedagogical practice for cultivating holistic education that supports intellectual, emotional, and social development.